Implementasi Konsep Impression of Tradition Culinary pada Interior Sentra Kuliner dan Oleh-Oleh khas Banjar di Kotabaru - Sella Andriani Oentung (Intra, 2016)
Kotabaru is one of the South Kalimantan districts, which has abundant natural resources and amazing nautical tourism. The existence of the potential possessed by Kotabaru is not followed by a facility that facilitate local culinary and souvenirs shop. Based on that fact, this design is created to facilitate a commercial place for Banjar’slocal culinary and souvenirs for tourists and people of Kotabaru. In creating the design of the interior, required a place that able to: present Banjar’s local culinary and souvenirs, which raised locality of Kotabaru’s value, have an educational value as a means of recognition and cultural preservation, also containing an entertainment value that makes visitors relax, comfort, and enjoying himself pampered by the ambience created by the design. Bylifting the local values of South Kalimantan, the designer hopes that it will help cultural preservation in Indonesia. The concept of Impression of the Culinary Tradition applied in order to give an experience and impressionfor visitors while tasting the foods as well as information provided, completed with the atmosphere of nature that contain elements of the Banjar’s local culture. The concept that deals with locality does not make a design stylized traditionally but it will be combined with modern style with deployment of technology and materials. The implementation of the concept on the design can be seen from the combination of geometrical shapes and forms taken from the concept of Banjar’s traditional house. The colors of the design are using typical colors that portray Banjar’s culture and some distinctive ornaments are applied on furniture and interior’s elements. Technology also applied to support educational problems. It will contain entertainment in order to give impressions for the users. Food Culinary and gift shop, named “KotabaruBungas”, is expected to be the pride of the community and become the identity of Kotabaru city. This place is also showing the beauty of diversity in culinary and cultural richness, so that it will be more famous in tourists and public’s destination